MANAGEMENT REGIME AND ITS IMPACT ON THE WETLAND FISHERIES IN ASSAM - CHANDRA, GANESH (Journal of the Inland Fisheries Society of India, 2020)
The floodplain wetlands (beels) in Assam extending over one lakh hectare, constitute the most important fishery resource of the state. These wetlands are the common property resource and under various management regimes, i.e., private management (individuals and groups), fishermen cooperative management, Community-based fisheries management (decentralized management, Government works as facilitator) and open access. Most of the unregistered beels are under open access. An impact study was undertaken in two wetlands of Assam under private and cooperative management regimes with the objectives of to assess the impact of management regimes on the productivity of the beel; to assess the economics of beel fisheries management; and to assess the impact on the livelihood of the fisher community of wetlands.An impact pathway was formulated for the impact analysis of management regimes on the productivity of the selected wetlands. The data were collected using structured questionnaire and focused group discussion with the lessee for privately managed beels and with secretaries for beels managed by Cooperatives. The productivity of Rawmari beel was 850 kg ha-1 yr-1 in comparison to 410 kg ha-1 yr-1 in Charan beel. The benefit accrued from private managed beels was better than the cooperative managed beels. This communication discusses in detail the positive and negative outcome of management regimes on the beel fisheries management. This communication also discusses about the sharing arrangement and benefit to community in the private and community managed wetlands.Key words: Floodplain wetland, common property resources, fisher, lessee, management regimes, productivity